Organizational Rewards in the Online Work Environment. Is There Any Chance of Full Accomplishment ? - Elena-Sabina Turnea (Ovidius University Annals: Economic Sciences Series, 2021)
When work is done at the employee’s home or elsewhere outside the official work environment, some organizational rewards disappear (such as interaction between colleagues, direct support from superiors, etc.), while there is a need for new rewards (technical support, payment for utilities, flexible work schedule, adequate work equipment, etc.). This paper main purpose is to analyze the literature review regarding the organizational rewards in the online work environment and to sketch the proper rewards that attract and maintain employees in the remotely online work. Many studies argue that employees are more productive when they work from home, but despite these, other authors declare vice versa. Even if the remote way of working brings somehow flexibility in employees’ s programs, there are cases that confirm that work from home involves longer hours programs than employees are paid, which can generate family problems (Crosbie and Moore, 2004). The main conclusions to which this paper reaches are: working remotely expects higher productivity, working remotely has many disadvantages, and to maintain employees when they work remotely, extra leisure time is needed.